An Analysis of Individual and Social Factors Affecting Occupational Accidents - Barkhordari, Amir (Saf Health Work, 2019)
BACKGROUND: Workforce health is one of the primary and most challenging issues, particularly in industrialized countries. This article aims at modeling the major factors affecting accidents in the workplace, including general health, work–family conflict, effort–reward imbalance, and internal and external locus of control. METHODS: A cross-sectional study was conducted in Esfahan Steel Company in Iran. A total of 450 participants were divided into two groups—control and case—and the questionnaires were distributed among them. Data were collected through a 7-part questionnaire. Finally, the results were analyzed using SPSS 22.0 and Amos software. RESULTS: All the studied variables had a significant relationship with the accident proneness. In the case group, general health with a coefficient of –0.37, work–family conflict with 0.10, effort–reward imbalance with 0.10, internal locus of control with –0.07, and external locus of control with 0.40 had a direct effect on occupational stress. Occupational stress also had a positive direct effect on accident proneness with a coefficient of 0.47. In addition, fitness indices of control group showed general health (–0.35), work–family conflict (0.36), effort–reward imbalance (0.13), internal locus of control (–0.15), and external locus of control (0.12) have a direct effect on occupational stress. Besides, occupational stress with a coefficient of 0.09 had a direct effect on accident proneness. CONCLUSION: It can be concluded that although previous studies and the present study showed the effect of stress on accident and accident proneness, some hidden and external factors such as work–family conflict, effort–reward imbalance, and external locus of control that affect stress should also be considered. It helps industries face less occupational stress and, consequently, less occurrence rates of accidents.